REKONSTRUKSI PERJANJIAN PRA NIKAH DALAM PERSPEKTIF HUKUM KELUARGA ISLAM TERHADAP HUKUM POSITIF - Muhammad Jawahir noor (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2025)
The advancement of information technology has led to the emergence of online marriage practices using live streaming methods, particularly during the COVID-19 pandemic. However, this phenomenon raises various legal issues from both Islamic law and Indonesian positive law perspectives. This study aims to examine the validity of online marriage based on the pillars and conditions of marriage in Islamic law, as well as to analyze the national legal framework regarding registration and the legality of such marriages. Using a normative juridical method and a descriptive-qualitative approach, the study finds that while some Islamic scholars permit online marriage under certain conditions—such as clear identity verification and the unity of the contract session virtually—Indonesia’s positive law has yet to regulate this practice comprehensively and permanently. This legal gap creates uncertainty and inconsistencies in practice. Therefore, harmonization between religious norms and state law is necessary to ensure that online marriages can be conducted legally, orderly, and with adequate legal protection for all parties involved.